Que “coisa” é essa? – usos e funções - Costa, Jose Walberico da Silva (2019)
We aim to investigate the lexical item "thing", a substantive linguistic element that is frequently used in syntagmatic constructions in the actual use of spoken language, especially in the context of oral interviews (the corpus of the Linguistic Variation in State of Paraíba - VALPB). In this sense, we direct our study to the functioning of this lexical item, in order to investigate it's use in the spoken language, since it is more fluid and natural. We used the assumptions of Classical Functional Linguistics (Givón, 2012; Furtado da Cunha and Tavares, 2014; Furtado da Cunha, Oliveira and Martelotta, 2015) and their categories of analysis to support our analysis of the occurrences collected. We also consider in this investigation the assumptions of Textual Linguistics, represented by Koch 1996. Our general objective is to examine the uses and functions of the lexical item "thing" in a corpus of spoken language. As specific objectives, we intend to: a. some notes of the lexical item “thing” in European Portuguese and Brazilian Portuguese, considering their records in letters, wills, donations and reports, as well as checking some entries in dictionaries from Latin to Portuguese and Portuguese, properly; b. to verify the motivation that underlying the choice of the speaker by the lexical item "thing" in the linguistic context, as well as in the communicative situation; c. to present the discursive function (s) in the contexts in which it is used and the influences of the communicative environment in its attribution of meaning; d. Analyze the syntactic, semantic and discursive-pragmatic functions of the lexical item "thing"; and. quantify the occurrences of "thing" in order to identify its prototypical use. Our research is qualitative basement with quantitative support, it is also bibliographic and descriptive and will follow the following steps: 1. Collection of the occurrences of the lexical item "thing" in the corpus; 2. Analysis of occurrences to know what functions and properties "thing" manifests in each of the grammatical levels observed; and 3. Establishment of the prototypical use of this lexical item according to the most frequent uses in the linguistic contexts noted. As conclusions, we affirm that the prototypical use of the lexical item "thing" in the syntax is of direct object and predicative; that its semantic properties are of an abstract and non-referential noun; that its informational status is unstable, since its information is equivalent to each other, that is, it depends very much on the use to know if the information is new, old or inferable, not having, therefore, the prototypic; and that its most frequent textual function is anaphoric.